EFL TEACHERS PERCEPTIONS TOWARD THE USE OF AUTHENTIC MATERIAL IN TEACHING READING COMPREHENSION - Mukhalladun, Wildanum; Nidawati, Nidawati; AR, Muhammad (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2020)
Reading comprehension is one of the english skills that cannot be neglected. Most students faced difficulties in understanding english written text. Therefore, the role of teachers and teaching material is significant. Teachers, as facilitators, have a big responsibility to provide and use teaching material besides textbooks, which are authentic materials. This research aims to find out EFL teachers perceptions of authentic materials in teaching reading. This research employed a qualitative research approach in which its data were qualitatively collected through questionnaires and interviews. The sample is 20 english teachers from several Senior High Schools in Aceh Besar who have more than three years of experience in teaching to fill questionnaires distributed via google form. Then, 3 teachers was chosen to interview to get some additional information via semi-structured interview. Based on both instruments, EFL teachers showed positive perceptions of using authentic materials in teaching reading. All of them had used authentic materials in their teaching. The reasons they used authentic materials because it could increase students motivation, interest and understanding english written text. Besides, the majority of teachers found some challenges in using authentic materials including lack of vocabulary, technical problem and time-consuming. Overall, teachers believe that authentic materials are beneficial in teaching reading comprehension.